Pencegahan penyalahgunaan narkotika di pemerintah Kota Prabumulih (evaluasi penerapan Instruksi Presiden Nomor 2 Tahun 2020) - Yulia Puspita Sari; Palupi Lindiasari Samputra (Publisia: Jurnal Ilmu Administrasi Publik, 2021)
This study aims to evaluate and identify the factors that influence Presidential Instruction Number 2 of 2020. The research used a qualitative approach with formative evaluation techniques, taking place in Prabumulih from November 2020 to January 2021. The results showed that the implementation of Inpres 2/2020 was not optimal because the Prabumulih government had only taken 10% of its actions as a P4GN Facilitator in Prabumulih. There are four inhibiting factors : the necessary size of the Presidential Instruction 2/2020, human resources at the Prabumulih City BNN, minimal budget for the P4GN Program, Implementers who have not carried out socialization actions, changes in budget policy priorities, and increased criminal activity due to economic factors. It is necessary to optimize the collaboration between the City BNN and Prabumulih City Government and strengthen social capital by involving the community.